Identification of a New HCV Subtype 6xg Among Injection Drug Users in Kachin, Myanmar - Ye, Mei; Chen, Xin; Wang, Yu; Duo, Lin; Zhang, Chiyu; Zheng, Yong-Tang (Frontiers in Microbiology, 2019)
Characterizing HCV genetic diversity not only allows us to trace its origin and evolutionary history, but also provides valuable insights into diagnosis, prevention and therapy of HCV infection. Although eight HCV genotypes and 86 subtypes have been classified, there are still some HCV variants that need to be assigned. The genotype 6 is the most diverse HCV genotype and mainly prevalent in Southeast Asia. In this study, we identified a new HCV subtype 6xg from injection drug users (IDUs) in Kachin, Myanmar. A distinctive feature of 6xg from other subtypes of the genotype 6 was a Lys insertion in NS5A gene, which changes the RRKR/K motif into RRKKR/K. Bayesian analyses showed that HCV 6xg originated during 1984-1988, and experienced a rapid population expansion during 2005-2009. We characterized HCV subtype profile among IDUs in this region, and detected six HCV subtypes, including 1a (12%), 3a (12%), 3b (24%), 6n (16%), 6xa (20%), and 6xg (12%). Importantly, we found that HCV subtype distribution in Kachin was very similar to that in Dehong prefecture of Yunnan, but very distinct from those in other regions of Myanmar and Yunnan, indicating that the China-Myanmar border region shared a unique HCV subtype pattern. The appearance of 6xg and the unique HCV subtype profile among IDUs in the China-Myanmar border region have significant epidemiological and public health implications.